Studies on mosaic disease of sunflower: Biochemical changes and growth parameters - A. SUDHAKARA RAO* and D.V.R. SAI GOPAL, U. BHAVANI, K. VENKATA SUBBAIAH (Indian Phytopathology, 2002)
Biochemical changes in chlorophylls, proteins, sugar and starch, lipids, and growth and yield, were determined in sunflowers infected by mosaic virus disease in India. It was concluded that the virus caused changes in the biochemical content of sunflowers which contributed to decreased growth.